2012
DOI: 10.1016/j.jcin.2012.07.015
|View full text |Cite
|
Sign up to set email alerts
|

CYP2C19*2 and *17 Alleles Have a Significant Impact on Platelet Response and Bleeding Risk in Patients Treated With Prasugrel After Acute Coronary Syndrome

Abstract: The present study shows a significant influence of CYP2C19*2 and *17 alleles on response to chronic treatment by prasugrel 10 mg daily and occurrence of bleeding complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
54
1
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 35 publications
5
54
1
3
Order By: Relevance
“…5,6 Yet, recent reports have shown some residual interindividual variability, despite prasugrel that could be because of other signaling pathways or genetic polymorphisms. 8,9 In this study, we corroborate with previous work that the presence of the CYP2C19*2 loss-of-function allele influences on treatment P2Y12-mediated platelet responses, and provide novel insights that α 2A -AR polymorphism mediates P2Y12-mediated platelet responses in stable coronary artery disease patients taking clopidogrel. Furthermore, in those individuals who carry both mutations, it is notable that there is an additive effect on the P2Y12-mediated platelet responses.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…5,6 Yet, recent reports have shown some residual interindividual variability, despite prasugrel that could be because of other signaling pathways or genetic polymorphisms. 8,9 In this study, we corroborate with previous work that the presence of the CYP2C19*2 loss-of-function allele influences on treatment P2Y12-mediated platelet responses, and provide novel insights that α 2A -AR polymorphism mediates P2Y12-mediated platelet responses in stable coronary artery disease patients taking clopidogrel. Furthermore, in those individuals who carry both mutations, it is notable that there is an additive effect on the P2Y12-mediated platelet responses.…”
Section: Discussionsupporting
confidence: 88%
“…[1][2][3][4] Although the interindividual variability has been reduced with the introduction of more potent P2Y12 inhibitors, such as prasugrel or ticagrelor, 5,6 variability continues to exist, 7 suggesting that other signaling pathways or genetic polymorphisms may be important. 8,9 Variability in platelet response has been partly attributed to the influence of environmental factors, such as smoking, body weight, and alcohol; however, genetic polymorphisms may play a crucial role as well. The cytochrome P450 2C19*2 (CYP2C19*2) loss-of-function allele exemplifies this with its known influence on ADP-induced platelet aggregation.…”
mentioning
confidence: 99%
“…Moreover, lower PRI VASP than noncarriers (25 ± 13% vs. 31 ± 15%, p = 0.03, p = 0.03), lower rate of HTPR (1% vs. 10%, p = 0.02), higher rate of hyper-response (34% vs. 21%, p = 0.02) were observed in CYP2C*17 carriers. CYP2C19*17 carriers had a higher rate of bleeding complications than non-carriers [66].…”
Section: Influence Of Cyp2c19 Snps On Prasugrel Metabolismmentioning
confidence: 90%
“…Moreover, 50% of patients with HPR during prasugrel therapy were carriers of the reduced-function allele CYP2B6*6, and 41.7% were carriers of CYP2C9*2 allele [65]. Cuisset et al [66] demonstrated that, among 213 patients undergoing stenting for ACS and treated with prasugrel 10 mg daily, CYP2C19 2 carriers had significantly higher PRI VASP than noncarriers (33 ± 15% vs. 27 ± 14%, p = 0.03) and higher prevalence of HPR (16% vs. 4%, p = 0.01). Moreover, lower PRI VASP than noncarriers (25 ± 13% vs. 31 ± 15%, p = 0.03, p = 0.03), lower rate of HTPR (1% vs. 10%, p = 0.02), higher rate of hyper-response (34% vs. 21%, p = 0.02) were observed in CYP2C*17 carriers.…”
Section: Influence Of Cyp2c19 Snps On Prasugrel Metabolismmentioning
confidence: 99%
“…CYP2C19*17 gain-of--function gene is related to a reactivity increase of clopidogrel, but recent studies found that this correlation may be due to CYP2C19*2 linkage disequilibrium [41]. However, prasugrel is not significantly influenced by gene polymorphism, although some studies suggest an association [42,43]. Subgroup analysis of TRITON-TIMI 38 did not find significant associations between common CYP variants and active metabolite levels, platelet inhibition, or clinical CV event rates [44].…”
Section: Genetic Detectionmentioning
confidence: 94%